Sistem Informasi Geografis (Sig) Pariwisata Kabupaten Bintan Berbasis Web - Yuddi; Liza Safitri (Jurnal Bangkit Indonesia, 2019)
Tourism has become a leading industry in Bintan Regency and is one of the fastest growing sectors in the service economy so that it can support and increase regional income, therefore promoting the existence of tourism objects is very important for the success of the tourism industry in Bintan Regency. Presentation of accurate information about the existence of tourist areas is needed as a guideline for tourists to visit the tourist area of Bintan Regency. One presentation of information about the existence of tourist areas is by displaying it in the form of data and information on geographical conditions known as Geographic Information Systems (GIS).The purpose of this study is to create a web-based geographic information system (GIS) regarding the existence of tourism objects in Bintan Regency by using a web-based mapping approach. In designing this geographic information system the author uses the Spiral method and in the analysis of system requirements modeled with UML (Unified Modeling Language) and implemented using the PHP programming language and MySQLI database.The results of the making of geographic information systems (GIS) regarding tourist areas in the Web-based Kaban Regency are expected to be a solution as a medium to promote the existence of tourist areas in Bintan Regency and also as a guide for tourists to visit these tourist areas.